Workshop Pelatihan Aplikasi Dapur Online - Sitanggang, Andri Sahata; Syafariani, R Fenny; Sari, Febilita Wulan; Hasti, Novrini (Jurnal Gema Ngabdi, 2022)
The impact given by COVID-19 is very widespread on culinary businesses, especially Rice Merchants, there is a decrease in the amount of income earned, influenced by changes in people’s buying culture, where people are now accustomed to using online purchases through applications. However, many traders also have limited technological knowledge skills and do not take advantage of good opportunities in using technology. So there must be a solution to deal with this problem. With the existence of technology counseling, training and mentoring and the application of application technology that makes it easier for rice traders/rice stalls to use the technology. This training is aimed at rice stall traders and the community through the Online Kitchen application. The training will be supported by assistance from the service team in registering merchant/consumer accounts, registering food/beverage menus, confirming orders, paying, sending and preparing reports. The method applied in this activity is to use the method of dialogue, discussion together, as well as training and assistance in using the application. This activity was carried out from 2 stages of training, 1. The first training was for rice stall traders and the second was training and mentoring for the community. The activity of making this application has the aim of making it easier for rice stall traders to use technology that increases online sales, so that traders do not only rely on direct sales on the spot.